Hypovolemic Shock in a Child: A Pediatric Simulation Case - Molly Rideout; William Raszka (Association of American Medical Colleges, 2018)
Introduction Volume depletion is a common problem in pediatrics. Interns need to be able to recognize critical illness such as hypovolemic shock, obtain access, and manage complications. This simulation case involves a child with hypovolemic shock who requires intraosseous (IO) needle placement. While designed for subinterns in pediatrics, it is relevant for clerkship students and interns in family medicine and emergency medicine. Methods In this case, a 3-year-old child presents with vomiting, diarrhea, and lethargy, and is in hypovolemic shock. As IV access cannot be obtained, he requires IO access. Laboratory results reveal hypoglycemia, hypernatremia, and acute kidney injury. Required equipment includes an IV arm task trainer and a child mannequin with IO capacity (or a child mannequin plus a separate IO task trainer). Learning objectives include recognizing and managing hypovolemic shock, hypoglycemia, and electrolyte disturbances; obtaining IO access; and communicating with a distraught parent. Critical actions include attempting IO access, requesting labs, and administering fluids. Students complete a selfassessment survey following the case. Results A pilot study was conducted in 2017 with all subinterns (N = 16) on the pediatric service. Students' perceived competence in assessment and management of volume depletion and procedural skills such as IO placement were high following the session, and students rated the case as a highly beneficial learning experience. Discussion This clinical simulation case allows students to demonstrate clinical reasoning skills, procedural skills, and management skills regarding hypovolemic shock. It may be used as part of a curriculum for fourth-year students entering pediatric residency.